The Sublethal Effects Of Meperfluthrin And Transfluthrin On Aedes Albopictus (Skuse) And Aedes Aegypti (Linnaeus) - Ang, Ching Yang (2017)
A laboratory study was conducted on the sublethal effects of meperfluthrin and transfluthrin on Aedes albopictus and Aedes aegypti. Several biological parameters of Ae. albopictus and Ae. aegypti were tested namely fecundity, fertility, pupation and emergence rate, sex ratio, blood feeding behavior and longevity. The LD50 value of meperfluthrin and transfluthrin obtained for Ae. albopictus was 0.0061 ng/mg and 0.0597 ng/mg, respectively. Whereas the LD50 value of meperfluthrin and transfluthrin obtained for Ae. aegypti was 0.0090 ng/mg and 0.0905 ng/mg, respectively.